2013
DOI: 10.2217/nnm.13.118
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in The Use of Liposomes for Tumor Targeting

Abstract: The use of liposomes for drug delivery began early in the history of pharmaceutical nanocarriers. These nanosized, lipid bilayered vesicles have become popular as drug delivery systems owing to their efficiency, biocompatibility, nonimmunogenicity, enhanced solubility of chemotherapeutic agents and their ability to encapsulate a wide array of drugs. Passive and ligand-mediated active targeting promote tumor specificity with diminished adverse off-target effects. The current field of liposomes focuses on both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
354
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(375 citation statements)
references
References 135 publications
2
354
0
5
Order By: Relevance
“…When autophagy occurs, a phagophore isolates cytoplasmic material (7) and closes on itself to form an autophagosome (8). These fuse with lysosomes to form an autolysosome (9) in which the cytoplasmic cargo is degraded. In this research article, nanoparticles are directly delivered to the cytoplasm of the cells by microinjection (10).…”
Section: Fig1mentioning
confidence: 99%
See 1 more Smart Citation
“…When autophagy occurs, a phagophore isolates cytoplasmic material (7) and closes on itself to form an autophagosome (8). These fuse with lysosomes to form an autolysosome (9) in which the cytoplasmic cargo is degraded. In this research article, nanoparticles are directly delivered to the cytoplasm of the cells by microinjection (10).…”
Section: Fig1mentioning
confidence: 99%
“…Since more than a decade, pharmacists, material scientists and biophysicists are intensively studying the design, preparation and cell biological behavior of nanosized particles carrying nucleic acids (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of liposomal nanoparticles has been shown to have no discernible impact on the characteristics of the entrapped drug 31 . Previous studies in this area have indicated that the trans-activating factor (TAT) could promote the cell internalization capability of liposomal nanoparticles 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been shown to influence and favor the EPR, for example, prolonged systemic circulation that allows longer interaction of liposomes with the target, size of the liposomes, composition, and charge on the surface of liposomes [12]. Longevity in blood is achieved by coating the liposomes with polymers, such as polyethylene glycol (PEG).…”
Section: Liposomes For Passive Tumor Accumulationmentioning
confidence: 99%